Epithelioid hemangioendothelioma of the spine: case report and review of the literature - Albakr, Abdulrahman (J Spine Surg, 2017)
Epithelioid hemangioendothelioma (EHE) has been described as a rare vascular bone lesion with histological features between hemangioma and high-grade angiosarcoma. Spinal EHE is a quite rare disease with few case reports and series reported in the literature. The tumor cells are positive for vimentin, CD31and CD34, factor VIII related antigen, ERG, and FLI1. Radiological features are not specific; it may appear as an osteolytic lesion. It can present as a multifocal disease in 40% of cases. No clear correlation with age and sex; however, it is slightly more common in males. Focal neck or back pain is the most common presenting symptom. The natural history of spinal EHE is unpredictable, and currently, there is no standard of care for treatment. Treatment options include preoperative embolization, and surgical resection followed by radiotherapy and/or chemotherapy. A 34-year-old previously healthy male presented with mid-thoracic back pain. Magnetic resonance imaging (MRI) of the spine revealed a decrease in vertebral body height at T5 with an enhancing mass. He underwent T5 balloon kyphoplasty and needle vertebral body biopsy. Results of the biopsy samples were non-diagnostic. Approximately 3 months after surgery, the patient presented with unsteady gait. A subsequent MRI revealed progression of the T5 compression fracture with cord compression. The patient subsequently underwent T4–T6 bilateral posterior decompression for epidural tumor and T3–T7 posterior instrumentation with pedicle screws. Pathology of the lesion revealed EHE. The patient was started on local radiation therapy (RT). On follow-up, 3 months after the second surgery, the thoracic spinal pain had improved dramatically. Our review highlights the diagnosis, clinical presentation, and treatment of spinal EHE. Complete resection is associated with good outcome. Radiotherapy has been used in partially resected lesions. However, the role of radiotherapy as primary treatment is not yet defined. Further studies should develop a treatment algorithm for this rare tumour.